Usability Testing Using Prototype Method in Smart Cleaning System Reporting Tegal Parang - Aldi Andres Ardiansah; Agung Triayudi; Ben Rahman (Jurnal Mantik, 2022)
Garbage includes final waste that is not used by the community, so it can cause disease if it is not handled properly. Garbage that is allowed to accumulate will emit an unpleasant odor. Several reports from the people of Jakarta, especially the South Jakarta area, do not litter. Garbage is often seen piling up on the streets or in public places. So that the development of a system with the concept of smart cleaning was formed, with the aim of reducing scattered waste that was dumped on the roadside and public places. The method used is SDLC in the form of a prototype model. System Design Methods with UML, Class Diagrams and Use Case diagrams. The results of the research are web- and mobile-based smart cleaning systems. The results of usability testing of the smart cleaning system obtained an average result of about 75% of the answers given by the respondents. The highest rating was obtained with a total percentage of 84% stating that the system can be read.